The Influence of Service Quality, Financing, and Compliance on Clinical Pathways Performance at Medika Dramaga Hospital, Bogor - Krishnafitria, Karlina; Djamil , Masyhudzulhak; Suherman, Suherman (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to know and analyze the influence of service quality, financing, and compliance on the performance of clinical pathways in Medika Dramaga Hospital Bogor. The samples for primary data taken were 100 JKN patients who were hospitalized with a diagnosis of Tuberculosis, DHF, PEB with SC, Hernia with Herniorrhoea, and BPH with TURP measures. Secondary data were taken from various sources, for variable service quality from the Marketing Unit report, Funding from the recap of data in inpatient billing, and CP compliance from the case manager data recap. Then the data were analyzed using the Partial Least Square method with the Confirmatory Factor Analysis (CFA) system. The results of the study on primary data show CFA reliability factor (0.941) is dominant in the service quality variable. Meanwhile in the secondary data, the service quality variable has a dominant CFA (0.902) compared to the financing variable and clinical pathways adherence to clinical pathways performance. From primary and secondary data the quality of service with 5 factors is the goal of quality service that has been proven to be dominant in influencing the performance of clinical pathways. Keywords : Clinical Pathways, Costs of Hospitalization , JKN Patients